(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
The modernization of Uzbekistan’s textile sector requires comprehensive analysis of blended yarn quality and performance. This research focuses on the structural and mechanical characterization of yarns produced from local Karakul wool blended with polyester and acrylic fibers. Advanced laboratory instruments, including Uster Tester-5, Statimat-C, and SEM imaging, were employed to evaluate tensile strength, elongation, evenness, and surface morphology. The results demonstrated that wool-polyester blends possess superior durability, while wool-acrylic yarns exhibit greater softness and warmth retention. By applying systematic testing and comparative evaluation, this study provides critical insights into optimizing yarn properties and ensuring high-quality standards in Uzbekistan’s textile industry.